Complex Strategic Choices Applying Systemic Planning for Strategic Decision Making - Leleur, Steen; SpringerLink (Online service) (London : Springer London, 2012)
Effective decision making requires a clear methodology, particularly in a complex world of globalisation. Institutions and companies in all disciplines and sectors are faced with increasingly multi-faceted areas of uncertainty which cannot always be effectively handled by traditional strategies. Complex Strategic Choices provides clear principles and methods which can guide and support strategic decision making to face the many current challenges. By considering ways in which planning practices can be renewed and exploring the possibilities for acquiring awareness and tools to add value to strategic decision making, Complex Strategic Choices presents a methodology which is further illustrated by a number of case studies and example applications. Dr. Techn. Steen Leleur has adapted previously established research based on feedback and input from various conferences, journals and students resulting in new material stemming from and focusing on practical application of a systemic approach. The outcome is a coherent and flexible approach named systemic planning. The inclusion of both the theoretical and practical aspects of systemic planning makes this book a key resource for researchers and students in the field of planning and decision analysis as well as practitioners dealing with strategic analysis and decision making. More broadly, Complex Strategic Choices acts as guide for professionals and students involved in complex planning tasks across several fields such as business and engineering.
Introduction: Complexity as a Challenge -- The Condition of Complexity -- Linking Complexity and Simplicity -- The Systemic Process -- The Systemic Toolbox -- Premises of Modelling Decision Support -- Company Relocation as Demo-case -- Summary and Perspective: Towards Robustness and Resilience.
Keywords: Engineering; Systems theory; Physics; Engineering economy; Business planning; Engineering; Engineering Economics, Organization, Logistics, Marketing; Organization/Planning.; Systems Theory, Control; Complexity